Duclauxin Derivatives From Fungi and Their Biological Activities - Shahid, Hamza; Cai, Teng; Wang, Yuyang; Zheng, Caiqing; Yang, Yuting; Mao, Ziling; Ding, Ping; Shan, Tijiang (Frontiers in Microbiology, 2021)
Duclauxin is a heptacyclic oligophenalenone dimer consisting of an isocoumarin and a dihydroisocoumarin unit. These two tricyclic moieties are joined by a cyclopentane ring to form a unique hinge or castanets-like structure. Duclauxin is effective against numerous tumor cell lines because it prevents adenosine triphosphate (ATP) synthesis by inhibiting mitochondrial respiration. There are about 36 reported natural duclauxin analogues mainly produced by 9 Penicillium and Talaromyces species (T. duclauxii, T. aculeatus, T. stipitatus, T. bacillisporus, T. verruculosus, T. macrosporus, P. herquei, P. manginii and Talaromyces sp.). These metabolites exhibit remarkable biological activities, including antitumor, enzyme inhibition, and antimicrobial, showing tremendous potential in agricultural and medical applications. This review highlights the chemical structures and biological activities of fungal duclauxins, together with biosynthesis, absolute configuration, and mode of action for important duclauxins. Furthermore, phylogenetic analysis and correct names of Penicillium and Talaromyces species producing duclauxins are presented in this review.